THE INFLUENCE OF BYZANTIUM ON THE ORTHODOXY OF KYIVAN RUS AND OLD RUSSIAN HAGIOGRAPHY - YURIY, Mykhailo; KHRISTAN, Nazar (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. Byzantium as a state existed for twelve centuries. More than a thousand years have passed since its inception and before Constantinople was taken by the Turks in 1453. In it, an independent socio-cultural version of the Christian faith, called "orthodoxy", was established and developed. The historical purpose of Byzantium was to adapt Christianity to the social and spiritual characteristics of the peoples who inhabited the lands east of Rome. Among her spiritual finds were several Slavic peoples and states. One of the spiritual "daughters" of Byzantium fell to Kyivan Rus. The set of properties and features that Russia inherited from Byzantium was named by the generalized term - Byzantium. Among the achievements that Russia inherited from the same Byzantium is the well-known principle of symphony, which means a special closeness of relations between the Church and the state. Initiated by the political doctrine and social strategy of the emperor Justinian I (483-565, ruled 527-565), it arose in the form of Caesaropapism, that is, the actual fusion of two branches of power: secular and spiritual, under different, from mild to brutal, forms of dominance of the first over the other It should also include hagiography, which is a well-known part of the ancient Russian written heritage, which was one of the main literary genres. Imitation of the Byzantine hagiographical canon (which manifested itself in the use of well-known language means, features of the words used, certain syntactic structures, peculiar stylistic conventions) makes it possible to talk about the stereotype of the genre created in the traditions of the Byzantine preaching life. In general, hagiographic literature occupies a special place in the genre system of Ancient Russia, demonstrating an excellent example of highly moral literature.